Emotional Marketing in Digital Space: A Domain Review of Effective Factors (Al-Mansour Journal, 2026)
This paper aims to identify a comprehensive landscape of theoretical and empirical development in the field of emotional marketing from 2010 to 2025. The methodology used is a Domain Review (Domain Review), which involves a systematic analysis of the content of 34 selected international articles sourced from prestigious academic databases. The data were extracted based on the subject criteria, methodology and Main results, and later classified in the Domain Review table. The thematic analysis identified nine macro-categories in the existing literature, the main of which are: the role of emotions in consumer behavior (29.4%) and the emotional bond/correlation between the brand and the consumer (26.5%). The results indicate that emotional marketing has escalated from a tactical level based on advertising messages to a strategic and technological one, and is now intertwined with concepts such as dynamic capabilities, organizational empathic ability, and new technologies such as artificial intelligence (AI) and virtual reality (VR). This study provides a theoretical and methodological basis for the development of new frameworks in emotional marketing.
Keywords: Emotional Marketing; Brand-Consumer Emotional Bond; Experientialism; Brand Empathy; Emotional Ethics